Vocational and Skills Education Status in India: Challenges and Opportunities for Vocational Education in India (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Vocational Education is based on occupation and employment and it is the need of the hour for every country to have strong vocational education system. It can be defined as skilled based education. Vocational Education helps in Economic growth. The Indian education system recognizes the role of education and particularly Vocational Education. National Council for Vocational Training, an advisory body, was set up by the Government of India plays its important role in implementation of Vocational Education in India. Although there are lots many areas in which India is facing problems in Vocational Education Implementation. This article throws light upon scope, problem areas and government role in Vocational Education Implementation. India has one of the largest technical manpower in the world. However, compared to its population it is not significant and there is a tremendous scope of improvement in this area. In India, the emphasis has been on general education, with vocational education at the receiving end. This has resulted in large number of educated people remaining unemployed. This phenomenon has now been recognized by the planners and hence there is a greater thrust on vocationalisation of education.